2011
DOI: 10.1002/mds.23477
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of cortical atrophy in patients with Parkinson's disease according to cognitive status

Abstract: These data suggest that cortical atrophy in PD exhibits a greater extent with increasing levels of cognitive impairment, and different anatomical substrates would correspond to each cognitive status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
100
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 25 publications
17
100
0
1
Order By: Relevance
“…Our results are in line with those in previous reports. According to previous imaging studies, patients with a shorter duration of parkinsonism before cognitive impairment in PD with dementia and PD-MCI had decreased GM volume in the PCC 11 and in the inferior parietal and orbitofrontal areas, 12 respectively.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our results are in line with those in previous reports. According to previous imaging studies, patients with a shorter duration of parkinsonism before cognitive impairment in PD with dementia and PD-MCI had decreased GM volume in the PCC 11 and in the inferior parietal and orbitofrontal areas, 12 respectively.…”
Section: Discussionmentioning
confidence: 89%
“…However, only a few structural imaging studies 11,12 have been conducted thus far to define anatomic candidates influencing the rate of cognitive decline in PD. These studies have revealed atrophy of the posterior cingulate cortex (PCC) 11 and inferior parietal and orbitofrontal areas 12 in patients with PD with shorter durations of parkinsonism before dementia and MCI, compared with those with longer durations of parkinsonism. These regions show considerable overlap with the default mode network (DMN), which is well-known to be disrupted in patients with AD.…”
mentioning
confidence: 99%
“…Varying degrees of atrophy have been reported in patients with PD without dementia, [41][42][43] with mixed evidence of an association between atrophy and neuropsychological measures. 44 Within a cohort of 90 patients with mild PD without dementia, we investigated SDGM volumes and cortical thickness and examined their associations with cognitive functioning and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have identified extensive gray matter volume loss in temporoparietal and prefrontal areas in PD-MCI compared with controls, 28 others detected small density reductions in the precuneus, primary motor, parietal cortex, 29 in addition to occipital areas, 30 or cortical thinning in focal frontal regions. 31 However, the small sample sizes, lack of consistent criteria for defining MCI, and the use of different measures of atrophy are among the parameters that could account for inconsistent findings among previous studies.…”
Section: Vertex-wise Comparisons Of Cortical Thickness Between (A) Comentioning
confidence: 99%